Nanostructured RF magnetron sputter deposited hydroxyapatite coating on the surface of permanent and biodegradable alloys - Surmenev R. A. Roman Anatolievich; Surmeneva M. A. Maria Alexandrovna; Selezneva I. I. Irina Ivanovna; Tyurin A. I. Aleksandr Ivanovich; Pirozhkova T. S. Tatjyana Sergeevna; Epple M. Mattias (2015, 2015)
Title screen